The Influence of Competence and Organizational Commitment on Achievement Motivation and Its Impact on Teacher Performance at SMP Negeri 17 Sarolangun - Yulinarti, Yulinarti; Zahari, M.; Sudirman, Sudirman (Dinasti International Journal of Digital Business Management, 2025)
This study aims to describe the competence, organizational commitment, achievement motivation and performance of teachers of SMP Negeri 17 Sarolangun and to determine and analyze the influence of competence and organizational commitment on achievement motivation and its impact on teacher performance at SMP Negeri 17 Sarolangun. This type of research uses descriptive verification research. This study uses the PLS analysis method. Based on the results of the descriptive analysis, it explains that the total competency score is 1949 in the high category. Then for the description of the organizational commitment variable, it shows that the organizational commitment of teachers at SMP Negeri 17 Sarolangun is high with a score of 1739. Furthermore, the description of the achievement motivation variable shows that the achievement motivation score is 2602 in the high category. While the description of the teacher performance variable shows that the score is 2596 in the high category. The results of the study indicate that competence and organizational commitment have a positive and significant influence on achievement motivation and teacher performance at SMP Negeri 17 Sarolangun. Increasing competence and organizational commitment encourages the creation of higher achievement motivation, which in turn contributes to improving teacher performance. In addition, achievement motivation itself has been proven to play an important role in strengthening the relationship between competence and organizational commitment with teacher performance, so that these factors are interrelated and together form optimal performance